Yenidoğan yoğun bakım ünitesi için gürültü önleme standardının geliştirilmesi ve sağlık profesyonellerinin uyumu ile yenidoğan konforuna etkisinin belirlenmesi - Arslan, Günay (My University, 2023)
Amaç: Araştırma, yenidoğan yoğun bakım ünitelerinde ortak bir dil oluşturulması ve her çalışanın bu doğrultuda hareket etmesi için yenidoğan yoğun bakım ünitelerine özgü bir gürültü önleme standartının geliştirilmesi amacıyla yapılmıştır. Yöntem: Tek grupta ön test-son test tasarımında yarı deneysel olarak gerekleştiririlen araştırmanın evrenini yenidoğan yoğun bakım ünitesinde görevli sağlık profesyonelleri (Hemşire, Hekim ve Ebeler) oluşturmuştur (n=42) ile 26 yenidoğan oluşturmuştur. Araştırmada üniteye özgü gürültü önleme standartı geliştirilmiş; konuyla ilgili eğitim verilmiş ve küvözlere gürültü kontrol cihazı yerleştirilmiştir. Eğitim öncesi ve sonrası gürültü önleme standartına uyum değerlendirilmiştir. Planlı ve plansız saatlerde gürültü seviyesi, nedeni ve cihazı uyarı veren küvöz de bulunan yenidoğanın yaşam bulguları ve konfor düzeyi kayıt edilmiştir. Sağlık profesyonelleri ise standarda uyum açısından araştırmacı ve yardımcı araştırmacı tarafından birbirlerinden bağımsız olarak değerlendirilmiştir. Bulgular: Çalışmanın bulgularına göre sağlık profesyonellerinin eğitim öncesi ve eğitim sonrası standarda uyum puanları arasında istatistiksel olarak ileri derecede anlamlı bir fark olduğu görülmektedir (p<0.001). Eğitim sonrası standarda uyum puanları eğitim öncesi puanlarına göre daha yüksek olarak saptanmıştır. Sağlık profesyonellerinin standarta uyumlarının artmasına ve gürültünün azalmasına karşın gürültünün yenidoğanların fizyolojik parametreleri (yenidoğanların kan basıncı, kalp atım hızı, SpO2, solunum sayısı, vücut ısısı) ve konfor puanına etkisi planlı ölçümlerle karşılaştırıldığında istatistiksel olarak anlamlı bir fark yaratmamıştır (p>0,05) ancak ortalama değerlerde düşüş görülmüştür. Plansız ölçümlerde ise eğitim sonrası ünitedeki standarta uyum arttığı ve gürültü azaldığı için yenidoğan fizyolojik parametreleri ve konforu olumlu yönde etkilendiği saptanmıştır.

Objective: The research was carried out in order to create a common language in neonatal intensive care units and to develop a noise prevention standard specific to neonatal intensive care units in order for each employee to act in this direction. Material and Method: The population of the study, which was carried out as a quasi-experimental in the pre-test-post-test design in a single group, consisted of health professionals (Nurses, Physicians and Midwives) working in the neonatal intensive care unit (n=42) and 26 newborns. In the research, a unit-specific noise prevention standard was developed; training was given on the subject and a noise control device was placed in the incubators. Compliance with the noise prevention standard was evaluated before and after the training.The vital signs and comfort level of the newborn, who was in the incubator with the noise level, cause and device warning during scheduled and unplanned hours, were recorded. Health professionals, on the other hand, were evaluated independently by the researcher and the assistant researcher in terms of compliance with the standard. Results: According to the results of the study, it was seen that there was a statistically significant difference between the standard compliance scores of health professionals before and after education (p<0.001). The scores of compliance with the standard after the training were found to be higher than the scores before the training. Despite the increase in the compliance of health professionals with the standard and the decrease in noise, the effect of noise on the physiological parameters of newborns (newborns' blood pressure, heart rate, SpO2, respiratory rate, body temperature) and comfort score did not make a statistically significant difference when compared with planned measurements (p>0.05). However, a decrease was observed in the mean values. In the unplanned measurements, it was determined that the newborn's physiological parameters and comfort were positively affected as the compliance with the standard in the unit increased and the noise decreased after the training. Conclusion: In this study, a noise prevention standard was developed for healthcare professionals; compliance with the standard was increased and noise was reduced by providing training on the implementation of the standard and noise.
Developing the noise prevention standard for the neonatal intensive care unit and determining the adaptation of health professionals and its effect on newborn comfort
Keywords: Bebek bakımı; Bebek, Yenidoğan; Gürültü; Gürültü kirliliği; Infant care; Infant, Newborn; Intensive care; Newborn; Noise; Noise pollution; Standard; Standart; Yenidogan; Yogun bakim